Influence of Additional Employee Income and Motivation on Employee Performance - Bintang Widia Oktavianto; Yuliati Yuliati (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
Additional Employee Income is one of the factors that influence the increase in employee performance. This study aims to determine the effect of additional employee income and motivation on employee performance at the Regional Asset Finance Agency of Malang Regency. This type of research uses quantitative. The population in this study is the Civil Servants of the Regional Asset Finance Agency of Malang Regency, amounting to 45 employees. The type of sample used in this study is a saturated sample, the scale item used is the Likert scale. Collecting data using a questionnaire. The analysis used is multiple linear analysis. The results of this study indicate that r arithmetic > table means that it is valid and the reliability is above 0.5 which means it is reliable while the results of the study show that the t-test results for the Additional Employee Income and Motivation variables have a positive effect on employee performance. The results of the F test show that the independent variables together have a positive effect on employee performance. The coefficient of determination (R2) shows the magnitude of the contribution of 0.543 to the Additional Employee Income and Motivation variables simultaneously on employee performance of 54.3 % and the rest is needed by other factors in the Regional Asset Finance Agency of Malang Regency.